Communication between Actors (Collaborative Governance) in Disaster Mitigation based on Sustainable Development at Batu City - Lestari, Asih Widi; Aji, Nawangsasi Wincahyo Artiko; Sukoco, Johan Bhimo (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Indonesia is geographically situated in a disaster-prone region due to its position at the convergence of multiple tectonic plates and its tropical climate, which features both wet and dry seasons. Natural disasters frequently impact areas with vulnerable populations, and such events often exacerbate the existing vulnerabilities within those communities. These vulnerabilities typically arise from unsafe physical environments, limited economic resources, and weak social structures. Internal and external pressures such as underdeveloped local institutions and a lack of essential disaster management skills further contribute to these risks. As part of national development efforts, disaster management policies encompass a continuum of actions taken before, during, and after disasters. In this context, the Batu City Government faces considerable challenges in managing recurring natural hazards. Despite the importance of proactive disaster risk reduction strategies, various implementation barriers persist. One critical aspect that requires improvement is routine disaster mitigation, which aims to reduce potential impacts and increase public awareness. An effective method is conducting regular outreach and education programs covering all disaster phases pre-disaster, emergency response, and post-disaster recovery. However, the local disaster management agency (BPBD) in Batu City infrequently conducts such awareness campaigns. Consequently, when disasters strike, the community often remains unprepared, leading to more severe consequences, financial losses, and even fatalities. To address these issues, it is essential for the Batu City Government to enhance its collaborative efforts with various stakeholders to ensure more robust and inclusive disaster mitigation measures.